Pengaruh Independensi Dan Profesionalisme Terhadap Hasil Audit - Puput Purnamasari; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
ABSTRACT This study aims to determine whether the independence and professionalism of an auditor has a positive effect on the quality of the auditor's audit results. The quality of good audit results usually also reflects the high quality of the auditor. At this time it is undeniable that audit quality is declining. This may occur due to several factors such as gratuities, bribes, and so forth. The research method used is a qualitative method by taking the technique of literature study or literature study. The source of this research is taken from the results of previous studies. This study resulted in the result that independence and professionalism have a positive influence on the quality of the auditor's audit results.